Psychological distress amongst AIDS-orphaned children in urban South Africa. - Cluver, L; Gardner, F; Operario, D (2007)
BACKGROUND: South Africa is predicted to have 2.3 million children orphaned by Acquired Immune Deficiency Syndrome (AIDS) by 2020 (Actuarial Society of South Africa, 2005). There is little knowledge about impacts of AIDS-related bereavement on children, to aid planning of services. This study aimed to investigate psychological consequences of AIDS orphanhood in urban township areas of Cape Town, South Africa, compared to control groups of children and adolescents orphaned by other causes, and non-orphans. METHOD: One thousand and twenty-five children and adolescents (aged 10-19) were interviewed using socio-demographic questionnaires and standardised scales for assessing depression, anxiety, post-traumatic stress, peer problems, delinquency and conduct problems. RESULTS: Controlling for socio-demographic factors such as age, gender, formal/informal dwelling and age at orphanhood, children orphaned by AIDS were more likely to report symptoms of depression, peer relationship problems, post-traumatic stress, delinquency and conduct problems than both children orphaned by other causes and non-orphaned children. Anxiety showed no differences. AIDS-orphaned children were more likely to report suicidal ideation. Compared to Western norms, AIDS-orphaned children showed higher levels of internalising problems and delinquency, but lower levels of conduct problems. CONCLUSIONS: Children orphaned by AIDS may be a particularly vulnerable group in terms of emotional and, to a lesser extent, behavioural problems. Intervention programs are necessary to ameliorate the psychological sequelae of losing a parent to AIDS.